2017
DOI: 10.1177/1038416217697972
|View full text |Cite
|
Sign up to set email alerts
|

Informing the career development of IT students by understanding their career aspirations and skill development action plans

Abstract: Attending university can assist students to make informed and realistic choices regarding their career. However, career development is a complex process and there are discipline-specific aspects to consider. In Information Technology, no clear career developmental pathway is evident in the literature despite recent efforts by employers, educators, and professional societies to help students improve their career expectations and employability upon graduation. This study aims to understand better the career aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 12 publications
0
24
0
1
Order By: Relevance
“…CAGC activities include career information provision, assessment and self-assessment tools, counselling interviews, and career education programs, "taster" programs that allow job-seekers to sample options, job search, and transition services. Due to the importance of CAGC for graduate employability, there have been several studies that examined the relationships between career education and graduate career aspirations and choices in multiple contexts (e.g., Bimrose & Hearne, 2012;McKenzie, Coldwell-Neilson & Palmer, 2017;Reddya & Rajaram, 2015). Solem, Kollasch, and Lee (2013) found that there were many organizational and businessoriented skills that employers value, but these were not commonly taught in graduate curricula in the USA HEI system.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…CAGC activities include career information provision, assessment and self-assessment tools, counselling interviews, and career education programs, "taster" programs that allow job-seekers to sample options, job search, and transition services. Due to the importance of CAGC for graduate employability, there have been several studies that examined the relationships between career education and graduate career aspirations and choices in multiple contexts (e.g., Bimrose & Hearne, 2012;McKenzie, Coldwell-Neilson & Palmer, 2017;Reddya & Rajaram, 2015). Solem, Kollasch, and Lee (2013) found that there were many organizational and businessoriented skills that employers value, but these were not commonly taught in graduate curricula in the USA HEI system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the importance of CAGC for graduate employability, there have been several studies that examined the relationships between career education and graduate career aspirations and choices in multiple contexts (e.g. Bimrose & Hearne, 2012; McKenzie et al., 2017; Reddya & Rajaram, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Curriculum-integrated CDL is widely acknowledged as enhancing student work-readiness (McKenzie, Coldwell-Neilson, & Palmer, 2017). An increasingly popular pathway is work-integrated learning (WIL; Harvey et al., 2017; Smith, Ferns, & Russell, 2014) where students formally engage in, and are assessed on, collaborative learning activities with industry and community partners.…”
Section: Introductionmentioning
confidence: 99%
“…The need to support tertiary ICT students with respect to career planning was explored in depth by McKenzie, Coldwell-Neilson and Palmer (2017). The results of their study affirms that many ICT students will need guidance to develop specific short-term actions that will support their long-term career goals.…”
Section: Efficacy Of Using Templatesmentioning
confidence: 92%